2011
DOI: 10.1097/coh.0b013e32834577b3
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells and regulatory T cells in elite control over HIV and SIV

Abstract: Purpose of review We present current findings about two subsets of CD4+ T cells that play an important part in the initial host response to infection with the human immunodeficiency virus type 1 (HIV): those producing IL-17 (Th17 cells) and those with immunosuppressive function (CD25+FoxP3+ regulatory T cells, or T-reg). The role of these cells in control of viral infection and immune activation as well as in prevention of immune deficiency in HIV-infected elite controllers will be examined. We will also discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 78 publications
2
53
0
Order By: Relevance
“…IL17, together with TNFα, has been shown to be an important cytokine in the host defense (Hartupee, Liu et al, 2007; Xu, Wang et al, 2012). Previous studies have shown that the IL17 producing cells were important for mucosal epithelial integrity during SIV and HIV infection (Brenchley, Paiardini et al, 2008; Hartigan-O’Connor, Hirao et al, 2011; Reeves, Rajakumar et al, 2011). Therefore, the loss of IL17 producing NKp44 + cells during infection in the gut may have a significant impact on gut homeostasis during SIV infection in macaques.…”
Section: Discussionmentioning
confidence: 99%
“…IL17, together with TNFα, has been shown to be an important cytokine in the host defense (Hartupee, Liu et al, 2007; Xu, Wang et al, 2012). Previous studies have shown that the IL17 producing cells were important for mucosal epithelial integrity during SIV and HIV infection (Brenchley, Paiardini et al, 2008; Hartigan-O’Connor, Hirao et al, 2011; Reeves, Rajakumar et al, 2011). Therefore, the loss of IL17 producing NKp44 + cells during infection in the gut may have a significant impact on gut homeostasis during SIV infection in macaques.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of Th17 cells was accompanied by a concomitant rise of Treg cells, resulting in an imbalanced Th17/Treg ratio during HIV progression [89,90,91]. A low Th17/Treg ratio in HIV-infected individuals correlates with microbial translocation and with a higher frequency of activated CD8 + T-cells, which is one of the strongest predictors of mortality.…”
Section: Bowel Conditions In People Living With Hivmentioning
confidence: 99%
“…We and others have shown IL-17-producing cells are preferentially depleted in the gastrointestinal (GI) tracts of HIV-infected humans and SIV-infected rhesus macaques (RMs) [57]. In contrast, Th17 cells are maintained at relatively normal levels in the GI tract of SIV-infected natural host species, HIV-infected long-term nonprogressors, as well as some patients on antiviral therapy [811].…”
Section: Introductionmentioning
confidence: 99%